Konsep Adab Menuntut Ilmu Prespektif Syaikh Muhammad Syakir Dlam Kitab Washayya Dan Implementasinya Dalam Mendidik Generasi Z & A - Siti Nur Kholiza; Ali Imron; Agus Maulana Firdaus (SPESIFIK: Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to 1) find out the adab concept of seeking knowledge according to Shaykh Muhammad Syakir in the Washayya book 2) find out the implementation of the adab of studying according to Shaykh Muhammad Syakir in the Washayya book in educating the Z & A generation. This research is a qualitative research in the form of library research. By using primary data sources directly from books, writings, journals, and so on, and secondary data, namely indirect sources providing data for data collection, through other people or documents. So the data collection technique includes searching for materials that are closely related to research, then followed by other data that are considered to support it. The data analysis used Content analysis (content analysis) and conclusions were drawn from this analysis.The results of the study show that the role of teachers and parents in educating the z & a generation is very influential. Both have the same task of educating, guiding and building morals or adab in learning. The Washayya book is one of many books that can be used as a reference or basis in educating the z & a generation. in its application in educating the z & a generation, parents and teachers must collaborate in order to create a generation with good morals.